Quantum gravity with matter fields in two dimensions - Bittner, Elmar; Janke, Wolfhard; Markum, Harald; Riedler, Jürgen (Geometry and Quantum Physics, 2000)
Spin systems coupled to two-dimensional manifolds are studied as a simple example for matter fields coupled to gravity. We consider two versions of quantum Regge calculus. The Standard Regge Calculus [1] where the quadratic link lengths q of the simplicial manifold vary continuously and the Discrete Regge Model [2] where they are restricted to two possible values. These manifolds are coupled with Z2 spins [3].
Gesehen am 18.10.2022